Searching for the Minimal Seesaw Models at the LHC and Beyond - Arindam Das (Advances in High Energy Physics)
The existence of the tiny neutrino mass and the flavor mixing can be naturally explained by type I Seesaw model which is probably the simplest extension of the Standard Model (SM) using Majorana type SM gauge singlet heavy Right Handed Neutrinos (RHNs). If the RHNs are around the Electroweak- (EW-) scale having sizable mixings with the SM light neutrinos, they can be produced at the high energy colliders such as Large Hadron Collider (LHC) and future 100 TeV proton-proton (pp) collider through the characteristic signatures with the same-sign dilepton introducing lepton number violations (LNV). On the other hand Seesaw models, namely, inverse Seesaw, with small LNV parameter can accommodate EW-scale pseudo-Dirac neutrinos with sizable mixings with SM light neutrinos while satisfying the neutrino oscillation data. Due to the smallness of the LNV parameter of such models, the “smoking-gun” signature of same-sign dilepton is suppressed where the RHNs in the model will be manifested at the LHC and future 100 TeV pp collider dominantly through the Lepton number conserving (LNC) trilepton final state with Missing Transverse Energy (MET). Studying various production channels of such RHNs, we give an updated upper bound on the mixing parameters of the light-heavy neutrinos at the 13 TeV LHC and future 100 TeV pp collider.